2010
DOI: 10.4049/jimmunol.0903345
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Nef Triggers Macrophage Fusion in a p61Hck- and Protease-Dependent Manner

Abstract: Macrophages are a major target of HIV-1 infection. HIV-1–infected macrophages form multinucleated giant cells (MGCs) using poorly elucidated mechanisms. In this study, we show that MGC formation was reduced when human macrophages were infected with nef-deleted HIV-1. Moreover, expression of Nef, an HIV-1 protein required in several aspects of AIDS, was sufficient to trigger the formation of MGCs in RAW264.7 macrophages. Among Nef molecular determinants, myristoylation was dispensable, whereas the polyproline m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 90 publications
4
84
1
Order By: Relevance
“…Because myeloid MGCs are characterized by specific concentrations of F-actin and the organization of their microtubules (17,30), we examined the cytoskeleton in placental MGCs. In pMw, F-actin was concentrated in dotted structures with a characteristic vinculin ring called podosomes (Fig.…”
Section: Pmw Mature Into Mgcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because myeloid MGCs are characterized by specific concentrations of F-actin and the organization of their microtubules (17,30), we examined the cytoskeleton in placental MGCs. In pMw, F-actin was concentrated in dotted structures with a characteristic vinculin ring called podosomes (Fig.…”
Section: Pmw Mature Into Mgcsmentioning
confidence: 99%
“…The cytoskeletal organization of placental cells was studied as described previously (30). Briefly, pMw and MGCs were permeabilized with 0.3% Triton X-100, incubated with mouse monoclonal anti-vinculin or anti-tubulin Abs (Sigma-Aldrich) for 1 h, and then incubated with Alexa 488-conjugated secondary Abs, phalloidin-Texas Red (Invitrogen), which specifically binds F-actin, and DAPI (Invitrogen) for 30 min.…”
Section: Cytoskeletal Organization Of Placental Cellsmentioning
confidence: 99%
“…Virus particles were produced by calcium-phosphate transfection of 293T cells, as described previously (37), using a plasmid coding for R5-tropic Bal Env glycoproteins inserted within the NL4-3 backbone (NL4-3Balenv) (38), a plasmid coding for wild type R5-tropic ADA or the same molecular clone of HIV-1 disrupted for the Nef open reading frame (ADADnef) (39,40). Cell-free supernatants were ultracentrifugated to eliminate free p24, resuspended in endotoxin-free PBS (Sigma-Aldrich), and quantified by an in-house double-Ab sandwich ELISA specific for the major core p24 protein (41).…”
Section: Virus Stocksmentioning
confidence: 99%
“…Nef is able to activate both Hck isoforms, leading to the formation of actin-rich protrusions and podosome rosettes (43). By activating p61Hck, Nef also triggers the fusion of individual infected macrophages, leading to the formation of giant multinucleated cells that could contribute to the establishment of latent virus reservoirs in some tissues (40). In addition, we recently showed that Nef expression in HIV-1-infected macrophages also resulted in a significant diminution of their phagocytosis ability (28).…”
mentioning
confidence: 99%
“…Infected macrophages also participate in the propagation of virus in nonlymphoid tissues, such as lungs or brain. Furthermore, we have recently shown that Nef expression during HIV-1 infection disturbs specialized functions of macrophages: (i) Nef induces the fusion of infected macrophages, leading to the formation of multinucleated giant cells through the activation of the Hck tyrosine kinase (40), and (ii) Nef also inhibits phagocytosis through the alteration of the polarized exocytosis of recycling endosomes regulated by AP-1 (28).…”
mentioning
confidence: 99%